Inadvertent hypothermia after endovascular therapy is not associated with improved outcome in stroke due to anterior circulation large vessel occlusion. (4th June 2021) - Hartmann, Christian; Winzer, Simon; Pallesen, Lars‐Peder; Prakapenia, Alexandra; Siepmann, Timo; Moustafa, Haidar; Theilen, Hermann; Barlinn, Jessica; Gerber, Johannes C.; Linn, Jennifer; Reichmann, Heinz; Barlinn, Kristian; et al.
Abstract: Background and purpose: Hypothermia may be neuroprotective in acute ischemic stroke. Patients with anterior circulation large vessel occlusion (acLVO) are frequently hypothermic after endovascular therapy (EVT). We sought to determine whether this inadvertent hypothermia is associated with improved outcome. Methods: We extracted data of consecutive patients (January 2016 to May 2019) who received EVT for acLVO from our prospective EVT register of all patients screened for EVT at our tertiary stroke center. We assessed functional outcome at 3 months and performed multivariate analysis to calculate adjusted risk ratios (aRRs) for favorable outcome (modified Rankin Scale scores = 0–2) and mortality across patients who were hypothermic (<36°C) and patients who were normothermic (≥36°C to <37.6°C) after EVT. Moreover, we compared the frequency of complications between these groups. Results: Among 837 patients screened, 416 patients received EVT for acLVO and fulfilled inclusion criteria (200 [48.1%] male, mean age = 76 ± 16 years, median National Institutes of Health Stroke Scale score = 16, interquartile range [IQR] = 12–20). Of these, 209 patients (50.2%) were hypothermic (median temperature = 35.2°C, IQR = 34.7–35.7) and 207 patients were normothermic (median temperature = 36.4°C, IQR = 36.1–36.7) after EVT. In multivariate analysis, hypothermia was not associated with favorable outcome (aRR = 0.99, 95% confidence interval [CI] = 0.75–1.31) and mortality (aRR = 1.18, 95% CI = 0.84–1.66). More hypothermic patients suffered from pneumonia (36.4% vs. 25.6%, p = 0.02) and bradyarrhythmia (52.6% vs. 16.4%, p < 0.001), whereas thromboembolic events were distributed evenly (5.7% vs. 6.8%, not significant). Conclusions: Inadvertent hypothermia after EVT for acLVO is not associated with improved functional outcome or reduced mortality but is associated with an increased rate of pneumonia and bradyarrhythmia in patients with acute ischemic stroke. Abstract : Hypothermia may be neuroprotective in acute ischemic stroke. In our study of 416 consecutive patients with anterior circulation large vessel occlusion, inadvertent hypothermia (temperature <36°C) compared to normothermia (36.0 to 37.5°C) after EVT was not associated with favorable outcome or mortality. Our study does not support the hypothesis that inadvertent hypothermia after EVT may have a potentially neuroprotective effect in this population.